2019
DOI: 10.1001/jamadermatol.2019.2983
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tape Strips to Detect Immune and Barrier Abnormalities in the Skin of Children With Early-Onset Atopic Dermatitis

Abstract: IMPORTANCE Molecular profiling of skin biopsies is the criterion standard for evaluating the cutaneous atopic dermatitis (AD) phenotype. However, skin biopsies are not always feasible in children. A reproducible minimally invasive approach that can track cutaneous disease in pediatric longitudinal studies or clinical trials is lacking. OBJECTIVE To assess a minimally invasive approach using tape strips to identify skin biomarkers that may serve as a surrogate to biomarkers identified using whole-tissue biopsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
209
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(220 citation statements)
references
References 114 publications
9
209
1
1
Order By: Relevance
“…This has been evaluated in two human AD studies, although both lack assessment of serum IL-34 correlation with severity. 13,14 The correlation of disease severity and serum IL-34 is consistent with evidence from a range of human inflammatory conditions such as rheumatoid arthritis (RA), inflammatory bowel disease, cutaneous lupus and ischemic cardiomyopathy. 7,10 Human patients with RA showed evidence of IL-34 induction at early diagnosis with further elevations linked to chronicity.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This has been evaluated in two human AD studies, although both lack assessment of serum IL-34 correlation with severity. 13,14 The correlation of disease severity and serum IL-34 is consistent with evidence from a range of human inflammatory conditions such as rheumatoid arthritis (RA), inflammatory bowel disease, cutaneous lupus and ischemic cardiomyopathy. 7,10 Human patients with RA showed evidence of IL-34 induction at early diagnosis with further elevations linked to chronicity.…”
Section: Discussionsupporting
confidence: 65%
“…[5][6][7][8][9][10][11] In these diseases, serum IL-34 concentrations were correlated with disease severity and high IL-34 was a poor prognostic marker. 12 Specific to skin diseases, IL-34 protein and gene expression was detected in both lesional, nonlesional and normal skin from adults and children with AD, 13,14 although no study has assessed serum IL-34 in these patients or looked at correlation with disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…This current study provides several novel findings. First, while tape-strips have been used to map the lesional and non-lesional AD cutaneous profiles at baseline ( 16 , 17 ), tape-strips have never been utilized to track molecular response to targeted treatment. Furthermore, the Olink proteomic assay, recently used to profile skin biopsies ( 28 ), has not yet been applied to analysis of tape-strips.…”
Section: Discussionmentioning
confidence: 99%
“…Tape-stripping, a minimally invasive approach that samples the stratum corneum and upper stratum granulosum (15,16), has been used to evaluate AD skin biomarkers, almost exclusively in untreated patients (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Koppes et al reported decreases in Th2 markers (e.g., IL-4, IL-13, CCL22) after local application of emollient to the skin (27).…”
Section: Introductionmentioning
confidence: 99%
“…AD displays a highly complex pathophysiology and heterogeneous phenotypes, which are illustrated by different features such as age of disease onset, variable response to triggers, spectrum of severity, barrier defect, potential of IgE autoreactivity and comorbidities (asthma, rhinitis, food allergy and infections) (1,2,3,4,5,6). Similar to asthma, AD research is developing and shaping precision medicine approaches aiming towards a biomarker based molecular taxonomy (7,8,9,10).…”
Section: Introductionmentioning
confidence: 99%